2020
DOI: 10.1007/s00221-020-05780-4
|View full text |Cite
|
Sign up to set email alerts
|

Motor timing training improves sustained attention performance but not fluid intelligence: near but not far transfer

Abstract: Associations between cognitive and motor timing performance are documented in hundreds of studies. A core finding is a correlation of about − 0.3 to − 0.5 between psychometric intelligence and time interval production variability and reaction time, but the nature of the relationship remains unclear. Here, we investigated whether this relation is subject to near and far transfer across a battery of cognitive and timing tasks. These tasks were administered pre-and post-five daily 30 min sessions of sensorimotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…However, it would be possible that nontemporal general factors mediate these correlations. In support of this notion, previous studies showed that psychometric intelligence is associated with temporal performance (Helmbold et al, 2007;Holm et al, 2011;Karampela et al, 2020;Rammsayer & Brandler, 2002;Ullén et al, 2008). Furthermore, other studies observed differential effects of behavioral conditions on perceptual and motor timing, suggesting the separability of their mechanisms (Bangert et al, 2011;Bueti & Walsh, 2010;Matthews, 2011;Repp, 2002).…”
Section: Introductionmentioning
confidence: 60%
“…However, it would be possible that nontemporal general factors mediate these correlations. In support of this notion, previous studies showed that psychometric intelligence is associated with temporal performance (Helmbold et al, 2007;Holm et al, 2011;Karampela et al, 2020;Rammsayer & Brandler, 2002;Ullén et al, 2008). Furthermore, other studies observed differential effects of behavioral conditions on perceptual and motor timing, suggesting the separability of their mechanisms (Bangert et al, 2011;Bueti & Walsh, 2010;Matthews, 2011;Repp, 2002).…”
Section: Introductionmentioning
confidence: 60%
“…Thus, future studies should consider assessing participants’ expectations before the intervention and controlling the effect of participants’ expectations on subsequent motor performances. Further, potential neurophysiological mechanisms underlying motor timing training effects tentatively include improved cognitive processes (e.g., attention and executive functions such as inhibitory control) and facilitated neural pathways in the critical brain regions that may contribute to various motor performances (Karampela et al, 2020; Sommer et al, 2014). Given that the corticomuscular coherence can effectively reveal functional connections between cortical regions and targeted muscles (Liu et al, 2019), investigating altered levels of corticomuscular coherence after interactive metronome training may provide more information on neurophysiological mechanisms underlying motor timing training effects on motor performances.…”
Section: Discussionmentioning
confidence: 99%
“…An ability to precisely regulate motor timing is essential for improving performances in many goal-directed movements, and this function contributes to movement accuracy and consistency in various motor control tasks (Karampela et al, 2020; Serrien & Spape, 2010). For example, open motor skills typically require optimal control of spatiotemporal timing to quickly adapt and correct motor actions in response to unexpected environmental changes (Brenner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%